2012
DOI: 10.5194/angeo-30-27-2012
|View full text |Cite
|
Sign up to set email alerts
|

A new method to derive middle atmospheric temperature profiles using a combination of Rayleigh lidar and O<sub>2</sub> airglow temperatures measurements

Abstract: Abstract. The vertical temperature profiles in a typical Rayleigh lidar system depends on the backscatter photon counts and the CIRA-86 model inputs. For the first time, we show that, by making simultaneous measurements of Rayleigh lidar and upper mesospheric O 2 temperatures, the lidar capability can be enhanced to obtain mesospheric temperature profile up to about 95 km altitudes. The obtained results are compared with instantaneous space-borne SABER measurements for a validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…We have found the same systematic 5-15 K warm bias in the lidar-satellite comparisons above 70 km found in studies like (García-Comas et al, 2014), (Taori et al, 2011), (Taori et al, 2012), (Taori et al, 2012), (Dou et al, 2009), (Remsberg et al, 2008), (Yue et al, 2014), and (Sivakumar et al, 2011). We have attempted to carefully account for the the background-induced warm bias in 315 high altitude Rayleigh lidar temperatures.…”
Section: )supporting
confidence: 73%
See 1 more Smart Citation
“…We have found the same systematic 5-15 K warm bias in the lidar-satellite comparisons above 70 km found in studies like (García-Comas et al, 2014), (Taori et al, 2011), (Taori et al, 2012), (Taori et al, 2012), (Dou et al, 2009), (Remsberg et al, 2008), (Yue et al, 2014), and (Sivakumar et al, 2011). We have attempted to carefully account for the the background-induced warm bias in 315 high altitude Rayleigh lidar temperatures.…”
Section: )supporting
confidence: 73%
“…(Taori et al, 2011(Taori et al, , 2012Taori et al, 2012) comprise an excellence series of publications using multiple instruments to measure the atmospheric temperature from 40 km to 100 km. These works found good agreement between the lidar and SABER up to 65 km and significant initialization errors in the lidar of up to 25 K near 90 km.…”
mentioning
confidence: 99%
“…c. Satellites, like MLS and SABER, provide globally distributed temperature measurements at several pressure levels throughout the vertical atmospheric column (Waters et al, 2006;Mertens et al, 2001). Satellite-based measurements provide a very good global view of the Earth's middle atmosphere, but can suffer from calibration errors, temporal coverage gaps, and problems with vertical resolution.…”
Section: Alternative Measurement Techniquesmentioning
confidence: 99%
“…The thermal structure of the mesosphere is important for short-period gravity wave features. To obtain background temperature profile in upper mesospheric altitudes, we have used the MLTP and Rayleigh lidar data available on 16 March 2012; from that, we retrieved the temperature from 14:04 UT to 19:38 UT with 30 min intervals (as described by Taori et al [2012]), shown in Figure 5. Together with the improved Rayleigh lidar temperature, we have used the spaceborne SABER temperature data for a wide grid encompassing 3°N to 23°N latitudes and 60°E to 100°E longitudes.…”
Section: Mesospheric Temperaturesmentioning
confidence: 99%